Effect of high strain rate on shear properties of carbon fiber reinforced composites. (8th February 2021) - Weng, Fei; Fang, Yingying; Ren, Mingfa; Sun, Jing; Feng, Lina
Abstract: With the Carbon Fiber Reinforced Polymer (CFRP) composites widely applied in the aerospace engineering field, it is necessary to get proper understanding of shear mechanical properties under dynamic loading. Taking the experimental method, this paper studied the in-plane and interlaminar shear properties of composites using a high-speed tensile test machine at high strain rate loading. Meanwhile, quasi-static tests were carried out with a universal test machine as contrast. Digital Image Correlation (DIC) method and high-speed camera were adopted to obtain the strains and the failure process of the specimen. This paper also designed a new method on interlaminar shear tests, with the experimental design, data processing and result analysis presented. The test results show that the strain rate sensitivity of the in-plane shear properties is greater than that of the interlaminar shear properties. The empirical formulas of high strain rate effects of CFRP materials were also derived for strength and modulus prediction and furtherly instruct the development of constitutive equations at various strain rates. In addition, this paper analyzed and discussed the failure mode of specimens, and the multiple-ply cracking, fiber pulling out and delamination in the V-shaped fracture has been shown in the in-plane shear tests while the typical mode II shear failure occurred in the interlaminar tests from strain rate range of 0.001–1500 s −1 . Graphical abstract: A new method to realize interlaminar shear tests of 0° laminated CFRP specimens is proposed in the paper and the evaluation of the test performance shows that it is suitable for dynamic testing for the polymer composites. Interlaminar shear test (a) Design of interlaminar shear test (b) Shear failure process of a specimen. Image 1